Developing an Evidence-Based Interprofessional Algorithm to Apply Noninvasive Ventilation in Acute Exacerbation of COPD - Farmer, Mary Jo S.; Callahan, Christine D.; Hughes, Ashley M.; Riska, Karen L.; Hill, Nicholas S. (CHEST pulmonary, 2024)
When administered as first-line intervention to patients admitted with acute hypercapnic respiratory failure secondary to COPD exacerbation in conjunction with guideline-recommended therapies, noninvasive ventilation (NIV) has been shown to reduce mortality and endotracheal intubation. Opportunities to increase uptake of NIV continue to exist despite inclusion of this therapy in clinical guidelines. Prior studies suggest that efforts to increase NIV use in acute exacerbation of COPD (AECOPD) need to account for the complex and interprofessional nature of NIV delivery and the need for interprofessional team coordination. We sought to develop an evidence-based interprofessional algorithm to apply NIV in AECOPD to improve the appropriate utilization of NIV in AECOPD. In this prospective qualitative descriptive study, subject matter expert physicians, nurses, and respiratory therapists practicing in a variety of clinical settings caring for patients with AECOPD were recruited for semistructured interviews. The Consolidated Criteria for Reporting Qualitative Research checklist was followed for interview development. Interview themes applicable to interprofessional collaborative practice were identified using deductive thematic analysis. An NIV algorithm based on recent society guidelines was constructed. Interprofessional team tasks appropriate for each phase of the NIV process were integrated into the algorithm. We present an interprofessional team-based algorithm for delivery of NIV in AECOPD inclusive of patient selection and initiation, titration, monitoring, and weaning of NIV. The goal is to increase appropriate uptake of NIV in the AECOPD population. The identified roles and responsibilities of an interprofessional team could be integrated into an interprofessional education program pertaining to use and management of NIV for patients with AECOPD emphasizing collaborative best practice, interprofessional team communication, and support of professional autonomy when appropriate.